Web development technique based on model of Object Oriented Data and Entities - Vega Fajardo, Adolfo Hans (2017)
Nowadays information systems are struggling to achieve the desired success, because one of its components is the development of web application struggle to be done, this is it because it takes a while for the creation of programming and once separately to create the data model, there is no technique that integrates both. Recent studies have shown that there are several programming techniques such as object oriented programming, aspect‐ oriented programming and programming targeted agents, and the creation of the data model are also techniques such as database connection object‐oriented entity, The this research aims to develop a web development technique based on database modeling object‐oriented model using entity relationship. Consequently, this study proposes two measures to validate the performance of web application development using analysis of variance, first the number of lines of programs created and the second response time database, led a group of students of the course web programming of the School of Universidad Nacional de Ingeniera UNI. The results obtained are expected to reach that software professionals have a means to strengthen their knowledge in the development of web application, likewise that information systems projects in the development stage of programming, has the desired success.